Social economics. - Hagenbuch, Walter ([Welwyn, Herts.] : J. Nisbet ; Cambridge. : Cambridge University Press, 1958)
Concerns with the problems of mankind in its ordinary everyday environment-with population, housing, working conditions, unemployment, poverty, social services, national insurance and assistance, and the welfare state.
Scope and meaning of social economics -- Population -- Housing -- Working conditions -- Unemployment -- Poverty -- Voluntary social services -- Public social services -- their structure and history -- National insurance and assistance -- Other public social services.
Includes bibliographical references (pages 307-309).
Keywords: Economics; Social history; Social problems